The school evasion in the amazon context: A case from a technical course - da Silva Júnior, Adonias Soares; Francisco Junior, Wilmo Ernesto [UNESP] (My University, 2018)
School dropout is a worrisome phenomenon at Brazilian public education, whose causes comprise different aspects. The present study analyzed the school dropout from a technical course in North of Brazil in order to minimize the rates. The data were gathered from documentary analysis and a questionnaire answered by evaded students. The outcomes showed 50% of school dropout. The main reasons were related to out of school factors, specially economic difficulties and due to work.
Análise da evasão escolar no contexto amazônico: O caso de um curso técnico
Keywords: Distance education; School dropout; Technical course